A positive electrode material of surface-modified lithium zirconate and preparation method thereof
By using liquid phase uniform coating method on high nickel positive electrode materials to form lithium zirconate cladding layer and bulk-phase gradient zirconium ion doping structure, the problem of structural instability of high nickel positive electrode materials during the H2-H3 phase transition is solved. , significantly improves its structural stability and electrochemical properties.
Patent Information
- Application Number
- CN202310105834.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-02-13
AI Technical Summary
High nickel positive electrode materials produce lattice shrinkage and volume deformation during the H2-H3 phase transition, resulting in microcracks and an unstable positive electrode/electrolyte interface, affecting the structural stability and electrochemical performance of the battery.
Using the method of uniformly coating high-nickel precursors based on the liquid phase of the organic system, the surface lithium zirconate solid electrolyte coating layer and bulk phase gradient zirconium ion doped structure is formed by one-step lithiation and phase sintering, and the surface state and bulk phase are regulated. structure.
It effectively improves the structural stability and electrochemical performance of high-nickel positive electrode materials, improves the cycle stability and rate performance, and reduces capacity loss and side reactions.
Smart Images

Figure HDA0004074767120000011 
Figure HDA0004074767120000012 
Figure HDA0004074767120000021
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode material of surface-modified lithium zirconate and a preparation method thereof, belonging to the technical field of new energy lithium-ion battery materials. Background Art
[0002] Over the past 30 years, lithium-ion batteries (LIBs) have made great progress, accelerating the transformation of my country's energy structure and expanding the application of clean energy. However, with the development of the times, future energy storage infrastructure is increasingly dependent on advanced lithium-ion battery cathode materials to achieve higher energy density, power density, longer cycle life and better safety. As one of the cathode materials currently widely used in electric vehicles, high nickel layered oxide (LiNi x Co y Mn z O 2 , x ≥ 0.8) due to its excellent capacity (200-250mAh g -1 ) and higher operating voltage (≈3.8V vs.Li 0 / Li + ), has significant advantages in energy density. By further increasing the Ni content, the theoretical specific capacity of the high-nickel cathode can be maximized, which is expected to break through the mileage bottleneck. At the same time, due to the high price and development difficulty of the Co element, people are committed to finding low-cost and high-capacity alternative cathode materials. Among them, replacing Co in the layered structure with other elements is an effective solution, which is expected to achieve better battery performance. Therefore, the development of high-specific-energy, high-nickel, and low-cobalt cathode materials is the future development direction.
[0003] In order to increase the compaction density and reduce the side reactions with the electrolyte, high nickel cathode materials are usually prepared into micron-sized spherical secondary particles formed by the accumulation of nano-sized primary particles. However, the H2-H3 phase transition at around 4.15V will cause a sharp contraction of the lattice in the c-axis direction and anisotropic volume deformation, resulting in microcracks between and within the crystals. The continued expansion of the cracks will cause the particles to crack to form open gaps, making it easier for the electrolyte to penetrate into the interior, and adverse side reactions will continue to occur inside and outside the particles to form an unstable cathode / electrolyte interface layer. In this process, the layered phase near the electrolyte side is due to Li + Problems such as uneven diffusion, oxygen loss, and increased cation mixing transform into an electrochemically inactive spinel / rock salt phase, further exacerbating the failure of electrode materials and continuous capacity decay. In addition, during the actual high-rate operation process, local heat accumulation will also accelerate the transformation of the layered structure to the inert rock salt phase, which is extremely unfavorable to the reaction kinetics of the material and the safety of the soft-pack battery level.
[0004] In order to further improve the structural stability of high-nickel materials, bulk doping, surface modification, construction of radially distributed microstructures, full concentration gradient design and other methods are currently used to control the surface interface structure and bulk lattice regulation. Among them, surface modification mainly uses oxides, phosphates, fluorides, conductive polymers and other species to coat high-nickel positive electrode materials to achieve the purpose of inhibiting side reactions, stabilizing surface lattice oxygen, and improving interface dynamics. However, these methods are still limited in improving the electrochemical performance of high-nickel materials. The main reasons are: ① Conventional coating methods usually introduce an inert oxide layer with low lithium ion conductivity, which is not conducive to interfacial charge transfer and will also lose some reversible capacity; ② Conventional coating methods are only based on simple blending, evaporation or hydrolysis of solid or liquid phases, lacking the means of kinetic control to construct a uniform coating layer with nanometer precision on the surface of the particles. The uncoated area will expose more reaction sites, resulting in poor protection effect; ③ Chemical vapor deposition (CVD) that can achieve uniform surface coating is expensive, the raw materials are expensive, and the deposition conditions are harsh, making it difficult to be compatible with existing battery production processes; ④ High-nickel materials, especially ultra-high nickel materials (Ni molar% ≥ 90%), are very sensitive to moisture and air. The general aqueous coating method will aggravate the corrosion and dissolution of active materials and the side reactions of residual lithium / bulk lithium on the surface with water and carbon dioxide in the solution and air, destroying the crystal structure and causing capacity loss; ⑤ There is a lack of effective methods for synchronously stabilizing the electrode / electrolyte interface and bulk lattice, and it is impossible to accurately control the surface interface structure.
[0005] To sum up, the development of a surface modification method based on liquid phase deposition with uniform and controllable thickness, simple operation and strong universality is of great significance to the development of lithium-ion battery positive electrode materials and electric vehicle industry. Summary of the invention
[0006] The purpose of the present invention is to provide a method for uniformly coating a high-nickel precursor in a liquid phase based on an organic system, forming a surface lithium zirconate solid electrolyte coating layer and a bulk gradient zirconium ion doped structure through a one-step lithiation phase sintering, while achieving regulation of the surface state and bulk structure of the particles, which can effectively improve the structural stability and electrochemical performance of the high-nickel positive electrode material.
[0007] The method for preparing the surface-modified lithium zirconate positive electrode material provided by the present invention comprises the following steps:
[0008] S1. preparing a solution A of a soluble zirconium salt;
[0009] S2, preparing solution B of precipitant 1 and precipitant 2;
[0010] S3, adding the hydroxide precursor material to the solution A, and ultrasonically dispersing to obtain a suspension;
[0011] S4, adding the solution B to the suspension to react;
[0012] S5, after the reaction in step S4 is completed, a precursor material with a surface coated with zirconium hydroxide is obtained by treatment;
[0013] The treatment includes steps such as centrifugation, washing, and drying;
[0014] S6. Mixing the precursor material of the surface-coated zirconium hydroxide with a lithium salt, and calcining to obtain the positive electrode material.
[0015] In the above preparation method, in step S1, the soluble zirconium salt is selected from at least one of the soluble metal zirconium salts containing metal zirconium element: zirconium nitrate, zirconium oxynitrate, zirconium sulfate, zirconium chloride, zirconium isopropoxide, zirconium n-butoxide, and zirconium acetate;
[0016] The amount of the soluble zirconium salt used is 0.2-4% of the molar amount of the hydroxide precursor material.
[0017] In the solution A, the concentration of the soluble zirconium salt is 1×10 -4 ~1mol / L, preferably 1×10 -3 ~0.02mol / L;
[0018] The solution A is obtained by dissolving the soluble zirconium salt at 5 to 120°C, preferably 40 to 60°C.
[0019] In the above preparation method, in step S2, the precipitant 1 and the precipitant 2 are independently selected from any one of the following:
[0020] Hexamethylenetetramine, urea, aqueous ammonia and dimethyl oxalate, preferably hexamethylenetetramine and urea;
[0021] The concentration of the precipitant 1 is 3×10 -4 ~3mol / L, preferably 3×10 -3 ~0.07mol / L;
[0022] The concentration of the precipitant 2 is 1.5×10 -4 ~1.5mol / L, preferably 1.5×10 -3 ~0.035mol / L;
[0023] The solution A and the solution B are prepared using a solvent with a volumetric water content of ≤0.4%:
[0024] Methanol, ethanol, isopropanol, ethylene glycol and diethylene glycol.
[0025] In the above preparation method, in step S3, the hydroxide precursor is selected from at least one of the precursors of lithium ion battery oxide positive electrode materials:
[0026] High nickel materials, lithium cobalt oxide, lithium nickel manganese oxide, lithium-rich manganese-based materials and lithium iron phosphate;
[0027] A nickel-cobalt binary hydroxide precursor in a high nickel material is preferred.
[0028] In the above preparation method, in step S4, the reaction temperature is 5 to 120° C., preferably 70 to 90° C., and the reaction time is 0.5 to 48 h, preferably 10 to 14 h.
[0029] In the above preparation method, in step S6, the lithium salt is any one of lithium oxide, lithium hydroxide, lithium hydroxide monohydrate and lithium carbonate.
[0030] In the above preparation method, in step S6, the molar ratio of the lithium salt to the surface-coated zirconium hydroxide precursor material is 1.0 to 1.15, preferably any value among 1.01, 1.03, 1.05 or a range value consisting of any two values thereof, wherein the molar amount of the surface-coated zirconium hydroxide precursor material is calculated as the sum of the molar amounts of each metal element therein;
[0031] The mixing method is wet mixing or dry mixing;
[0032] The solvent used in the wet mixing is at least one of ethanol, isopropanol or methanol.
[0033] In the above-mentioned preparation method, in step S6, the calcination atmosphere is at least one of air and oxygen;
[0034] The calcination includes a first calcination and a second calcination;
[0035] The conditions of the first step calcination are as follows:
[0036] The temperature is 200-700°C, the time is 0.5-10h, and the heating rate is 1-10°C / min;
[0037] The temperature is preferably 400-600°C, the time is preferably 3-6h, and the heating rate is preferably 2-5°C / min;
[0038] The conditions of the second step calcination are as follows:
[0039] The temperature is 400-1000°C, the time is 0.5-20h, and the heating rate is 1-10°C / min;
[0040] The temperature is preferably 700-900° C., the time is preferably 10-14 h, and the heating rate is preferably 2-5° C. / min.
[0041] The present invention avoids the high sensitivity of high-nickel finished products to humidity and air by treating high-nickel hydroxide precursors; realizes the ability to control the surface with nanometer precision through a kinetic control method, and then combines the subsequent lithiation one-step sintering to transform the coating layer into a solid electrolyte interface, thereby realizing penetration doping from surface coating to bulk phase.
[0042] The present invention provides a method for double precipitant-assisted precipitation based on non-aqueous solvents, wherein two precipitants undergo coordination condensation reaction with soluble zirconium salts during heating, and the two precipitants react with each other during the reaction to generate resin products, thereby promoting the positive shift of chemical equilibrium, accelerating the decomposition of the precipitant, and greatly improving the precipitation efficiency of zirconium ions. Through the screening of solvents and the kinetic regulation of the concentration of each component, the method can achieve uniform coating of zirconium-containing hydroxide on the surface of a spherical high-nickel hydroxide precursor, and its thickness can be regulated within a nanometer precision range, avoiding the reaction heterogeneity caused by point-like coating.
[0043] The positive electrode coating structure of the present invention has a surface-enriched phase gradient doping. Oxygen calcination is used during the sintering process to increase the valence state of the Ni element and inhibit the mixing of Li / Ni cations. At the same time, the electrochemically inert zirconium element penetrates into the surface lattice during the phase formation process and occupies the transition metal layer, playing a supporting role in charging and discharging, and alleviating the irreversible phase change.
[0044] In the present invention, surface zirconium ion doping is beneficial to refining the primary grains inside the finished secondary spherical particles, so that the (104) plane grows preferentially, the internal primary particles present a slender needle-like morphology and are stacked and arranged, thereby improving the mechanical strength of the particles and alleviating breakage caused by multiple charge and discharge cycles.
[0045] The lithium zirconate coating layer formed on the surface of the positive electrode particles in the present invention protects the positive electrode material and avoids direct contact with the electrolyte. In addition, unlike the traditional inert oxide coating layer, the modified layer has lithium ion conductivity, the surface coating and bulk phase gradient doping samples have a small reversible capacity loss, the coating layer is highly compatible with the substrate, and it is avoided to fall off during multiple charge and discharge cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a scanning electron microscope (SEM) image of the high-nickel binary hydroxide precursor material coated with zirconium hydroxide in Example 1.
[0047] Figure 2 This is a scanning transmission electron microscope bright field image (STEM-BF) of the high nickel binary hydroxide precursor material coated with zirconium hydroxide before calcination in Example 1.
[0048] Figure 3This is an X-ray energy dispersive spectrometry (EDS) image of the high nickel binary hydroxide precursor material coated with zirconium hydroxide before calcination in Example 1.
[0049] Figure 4 This is the X-ray diffraction (XRD) pattern of the zirconium-modified high-nickel polycrystalline positive electrode material in Example 1.
[0050] Figure 5 This is a scanning electron microscope (SEM) image of the high-nickel polycrystalline positive electrode material modified with lithium zirconate in Example 1.
[0051] Figure 6 This is a cross-sectional scanning electron microscope (SEM) image of the high-nickel polycrystalline positive electrode material modified with lithium zirconate after calcination in Example 1.
[0052] Figure 7 This is a transmission electron microscope (TEM) image of the surface of the high-nickel polycrystalline positive electrode material modified with lithium zirconate after calcination in Example 1.
[0053] Figure 8 This is an X-ray energy dispersive spectrum analysis (EDS) image of the high-nickel polycrystalline positive electrode material modified with lithium zirconate after calcination in Example 1.
[0054] Fig. 9 The charge and discharge curves of the high nickel polycrystalline positive electrode materials in Example 1 and Comparative Example 1 at a rate of 0.1C.
[0055] Fig.10 1 is a cycle diagram of the high nickel polycrystalline positive electrode material in Example 1 and Comparative Example 1 at a rate of 0.5C.
[0056] Fig.11 1 is a cycle diagram of the high nickel polycrystalline positive electrode material in Example 1 and Comparative Example 1 at 1C rate. DETAILED DESCRIPTION
[0057] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0058] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0059] The volumetric water content of ethanol used in the following examples is 0.15%. The comparative experiment of the present invention on ethanol water content of 0.4-0.8% shows that when the ethanol water content is higher than 0.6%, the zirconium hydroxide phase separation is obvious, which is not conducive to the formation of the coating layer, and 0.4% is not completely phase separated.
[0060] Embodiment 1,
[0061] (I) Preparation of positive electrode materials
[0062] At 45°C, 200 mg of zirconium nitrate pentahydrate was dissolved in 30 mL of anhydrous ethanol and stirred to obtain a clear and transparent solution, wherein the concentration of zirconium nitrate was 0.0155 mol / L. In addition, 196 mg of hexamethylenetetramine and 42 mg of urea were dissolved in 20 mL of anhydrous ethanol at room temperature and ultrasonically dissolved and dispersed to obtain a clear and transparent precipitant solution, wherein the concentration of hexamethylenetetramine was 0.07 mol / L and the concentration of urea was 0.035 mol / L. 2.2 g of Ni was accurately weighed. 0.905 Co 0.095 (OH) 2 The polycrystalline precursor is ultrasonically dispersed in 30 mL of zirconium salt solution; 20 mL of precipitant solution is added to the above solution, stirred and reacted at 80°C for 12 hours, and the precursor powder coated with zirconium hydroxide is obtained after centrifugation, washing with anhydrous ethanol, and drying; the modified precursor powder and lithium hydroxide monohydrate are mixed evenly in a mortar by an isopropanol wet method at a molar ratio of 1:1.01, and the powder is placed in a corundum crucible after volatilization and drying, and the temperature is increased to 500°C at 5°C / min in an oxygen atmosphere of a tube furnace and calcined for 5 hours, and then the temperature is increased to 720°C at 2°C / min and calcined for 12 hours, and finally cooled to room temperature at a cooling rate of 2°C / min, and ground with a mortar to obtain a positive electrode material modified with lithium zirconate and doped with zirconium gradient.
[0063] In this embodiment, the amount of zirconium nitrate added is Ni 0.905 Co 0.095 (OH) 2 2% by molar amount.
[0064] (II) Structural and morphological characterization
[0065] The precursor coated with zirconium hydroxide was characterized by scanning electron microscopy (SEM-8100). Figure 1 As shown, it can be seen that the needle-like texture of the precursor particles becomes blurred and a layer of coating species is deposited on the surface, but the original spherical morphology is still maintained after modification.
[0066] The surface morphology was further characterized by transmission electron microscopy (TEM-JEOL2100F). Figure 2 As shown, it can be seen that the thickness of the amorphous zirconium hydroxide coating layer is about 15 nm.
[0067] Energy dispersive X-ray spectroscopy (EDS) confirmed that Ni 0.905 Co 0.095 (OH) 2 There is a continuous and uniform Zr coating layer on the surface of the precursor.
[0068] The Zr-modified finished product LiNi after mixed lithium calcination was analyzed by powder X-ray diffractometer (D8 Advance, Brune) 0.905 Co0.095 O 2 (NC91) The crystal structure of the positive electrode, such as Figure 4 As shown, it can be seen that the prepared material has typical layered ternary material diffraction peaks, the (003) / (104) peak intensity ratio is greater than 1.2, and the structural order is good.
[0069] According to scanning electron microscopy Figure 5 It can be seen that the positive electrode material prepared by calcination continues the spherical morphology of the precursor.
[0070] Cross-sectional scanning electron microscopy Figure 6 This indicates that the interior of the positive electrode material prepared by calcination is mostly composed of needle-shaped primary particles.
[0071] The surface morphology was further characterized by electron microscopy. Figure 7 As shown, a lithium zirconate heterogeneous layer of about 1 nm is formed on the surface, and the surface lattice is obviously reconstructed.
[0072] X-ray spectroscopy ( Figure 8 ) proves that Zr is enriched on the surface and partially penetrates into the bulk phase.
[0073] (III) Battery assembly
[0074] The prepared positive electrode material is mixed with the binder polyvinylidene fluoride (PVDF, solef) and the conductive agent Super-P in a mass ratio of 8:1:1, and an appropriate amount of solvent N-methylpyrrolidone (NMP) is added to prepare a slurry. Using aluminum foil as the current collector, the slurry is evenly coated on the aluminum foil and vacuum dried at 80°C for 12 hours to obtain the positive electrode. The electrode is then cut into discs with a diameter of 10 mm using a punch, and the active material loading is about 3.3 mg / cm 2 The metal lithium sheet was used as the negative electrode, the polypropylene / polyethylene / polypropylene three-layer microporous membrane (Celgard 2325) was used as the separator, and 1 mol / L LiPF containing 1 wt% VC additive was used. 6 EC / EMC (v / v=3:7) was used as the electrolyte and button cells were assembled in an argon-protected glove box.
[0075] (IV) Performance test
[0076] The assembled battery was tested on a LAND charge and discharge tester with a constant current charge and discharge rate of 0.1C (1C = 200mA / g) and a charge and discharge range of 2.8-4.3V. The charge and discharge curve of the first cycle is shown in Figure 1. Fig. 9 As shown in the figure, it can be seen that the discharge capacity of the Zr-modified NC91 cathode material reaches 212.1 mA h / g. The capacity retention rate after 120 cycles at 0.5C rate is 93% (as shown in the figure). Fig.10The capacity retention rate after 200 cycles at 1C rate is 89.5% (as shown in Fig.11 This indicates that the positive electrode material has good cycle stability.
[0077] Embodiment 2,
[0078] It is basically the same as Example 1, except that Ni 0.905 Co 0.095 (OH) 2 The amount of the polycrystalline precursor used was 4.3 g. The thickness of the amorphous zirconium hydroxide coating layer was about 8 nm.
[0079] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0080] Embodiment 3,
[0081] It is basically the same as Example 1, except that Ni 0.905 Co 0.095 (OH) 2 The amount of the polycrystalline precursor used was 1.7 g. The thickness of the amorphous zirconium hydroxide coating layer was about 25 nm.
[0082] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0083] Embodiment 4,
[0084] It is basically the same as Example 1, except that Ni 0.905 Co 0.095 (OH) 2 The amount of the polycrystalline precursor used was 1.4 g. The thickness of the amorphous zirconium hydroxide coating layer was about 36 nm.
[0085] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0086] Embodiment 5,
[0087] It is basically the same as Example 1, except that in the second calcination step, the calcination time is adjusted to 8 hours.
[0088] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0089] Embodiment 6,
[0090] The method is basically the same as Example 1, except that in the second calcination step, the calcination temperature is adjusted to 700°C.
[0091] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0092] Embodiment 7,
[0093] The method is basically the same as Example 1, except that the molar ratio of the modified precursor powder to lithium hydroxide monohydrate is 1:1.03.
[0094] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0095] Embodiment 8,
[0096] The method is basically the same as Example 1, except that the molar ratio of the modified precursor powder to lithium hydroxide monohydrate is 1:1.05.
[0097] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0098] Embodiment 9,
[0099] It is basically the same as Example 1, except that the molar ratio of the modified precursor powder to lithium hydroxide monohydrate is 1:1.07.
[0100] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0101] Embodiment 10
[0102] The method is basically the same as Example 1, except that natural cooling is adopted after calcination.
[0103] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1.
[0104] Comparative Example 1
[0105] At room temperature, accurately weigh 2.2 g Ni 0.905 Co 0.095 (OH) 2 The polycrystalline precursor was ultrasonically dispersed in 50 mL of anhydrous ethanol, stirred and reacted at 80°C for 12 hours, and the cathode material powder was obtained after centrifugation, anhydrous ethanol washing and drying. The precursor powder and lithium hydroxide monohydrate were mixed evenly in a mortar by an isopropanol wet method at a molar ratio of 1:1.01. After volatilization and drying, the powder was placed in a corundum crucible, heated to 500°C at 5°C / min in an oxygen atmosphere of a tube furnace and calcined for 5 hours, then heated to 720°C at 2°C / min and calcined for 12 hours, and finally cooled to room temperature at a cooling rate of 2°C / min, and ground with a mortar to obtain an unmodified cathode material.
[0106] The battery was assembled and tested for performance according to the method in Example 1. The results are shown in Table 1. Figure 9-11 shown.
[0107] Table 1 Cyclic stability of the batteries in Examples 1-10 and Comparative Example 1
[0108] 1C first cycle discharge capacity (mA h / g) Discharge capacity after 100 cycles at 1C (mA h / g) Capacity retention rate (%) Example 1 191.3 184.3 96.3 Example 2 193.8 184.3 95.1 Example 3 186.7 148.6 79.6 Example 4 152.9 112.9 73.8 Example 5 189.2 113.4 59.9 Example 6 187.4 67.0 35.8 Example 7 192.2 178.5 92.9 Example 8 190.6 165.1 86.6 Example 9 187.3 155.1 82.8 Example 10 194.8 175.1 89.9 Comparative Example 1 188.2 165.6 88.0
[0109] The following conclusions can be drawn from the data in Table 1:
[0110] By comparing Examples 1-2 with Comparative Example 1, it can be seen that the strategy of surface lithium zirconate modification combined with partial zirconium doping can effectively improve the cycle stability of high-nickel positive electrode materials without sacrificing their theoretical specific capacity. The reason may be that the electrochemically inert zirconium ion doping penetrates into the surface lattice, enhancing the surface structural stability during the delithiation process. At the same time, the introduction of tetravalent zirconium ions induces surface nickel reduction to form a chemically inert rock salt phase, which inhibits the side reactions between the electrolyte and the positive electrode surface. The tightly packed internal microstructure of the needle-shaped primary particles formed by zirconium doping effectively relieves the accumulated stress during the charge and discharge process, improves the mechanical strength of the material, and prevents particle fragmentation. The lithium zirconate modification layer formed in situ during the mixed lithium calcination process can act as an ion conductor, effectively reducing the interfacial charge transfer impedance, thereby improving the rate performance of the material. The combination of surface modification and lattice doping synergistically improves the cycle stability of high-nickel materials.
[0111] By comparing Examples 1-4, it can be seen that there is an optimal value for the content of the introduced zirconium element. If the content of zirconium hydroxide coated on the precursor is too high, the surface will be reconstructed into a rock salt phase in large quantities, consuming too much active lithium, which is not conducive to capacity utilization and interfacial charge transfer, and ultimately manifests as low capacity and poor cycle stability, such as Examples 3 and 4; when the content of zirconium hydroxide coated on the precursor is low, very little lithium zirconate phase is formed, the surface reconstruction is not obvious, and the optimal protection effect cannot be achieved; long cycle tests show that the advantages of Example 1 are more obvious than those of Example 2.
[0112] By comparing Example 1 with Examples 5-6, it can be seen that there are optimal values for calcination temperature and calcination time. If the calcination time is too short, the residual alkali content of the material is high, the lithium phase formation is incomplete, and the structural order is poor, resulting in low discharge specific capacity and capacity "diving" phenomenon. If the calcination temperature is too low, there are also disadvantages such as high residual alkali content of the material, serious cation mixing, and insufficient phase formation, resulting in more serious reduction in discharge specific capacity and capacity diving phenomenon.
[0113] By comparing Example 1 with Examples 7-9, it can be seen that there is an optimal value for the amount of lithium salt added. As the amount of lithium salt added increases, the amount of residual alkali after calcination gradually increases, the primary grains gradually become coarser, and the particles are more easily broken, which is not good for the mechanical stability of the material, thereby causing a decrease in capacity retention. When the amount of lithium salt added is too high (>1.05), the first cycle capacity and first efficiency decrease significantly. At this time, due to the excessive residual alkali, the battery polarization is large, and the side reaction between the positive electrode material and the electrolyte is obvious.
[0114] By comparing Example 1 with Example 10, it can be seen that it is necessary to control the calcination cooling rate. In the natural cooling process, the electrode material particles will be subjected to greater stress during the cooling process, and the particles are more easily broken. At the same time, the natural cooling has a shorter residence time in the high temperature zone, which is not conducive to the removal of surface residual alkali and surface lattice reforming. Therefore, it is necessary to select an appropriate cooling method.
Claims
1. A method for preparing a surface-modified lithium zirconate positive electrode material, comprising the following steps: S1. preparing a solution A of a soluble zirconium salt; In step S1, the soluble zirconium salt is selected from at least one of the soluble metal zirconium salts containing metal zirconium element: zirconium nitrate, zirconium oxynitrate, zirconium sulfate, zirconium chloride, zirconium isopropoxide, zirconium n-butoxide, and zirconium acetate; The solvent of the solution A is anhydrous ethanol; S2, preparing solution B of precipitant 1 and precipitant 2; In step S2, the precipitant 1 and the precipitant 2 are independently selected from any one of the following: Hexamethylenetetramine and urea; S3, adding the hydroxide precursor material to the solution A, and ultrasonically dispersing to obtain a suspension; The hydroxide precursor is a nickel-cobalt binary hydroxide precursor; The amount of the soluble zirconium salt is 2% of the molar amount of the hydroxide precursor material; S4, adding the solution B to the suspension to react; S5, after the reaction in step S4 is completed, a precursor material with a surface coated with zirconium hydroxide is obtained by treatment; S6, mixing the precursor material of the surface-coated zirconium hydroxide with lithium hydroxide monohydrate, and calcining to obtain the positive electrode material; The calcination includes a first step calcination and a second step calcination; The conditions of the first step calcination are as follows: The temperature is 500 °C, the time is 5 h, and the heating rate is 5 °C / min; The conditions of the second step calcination are as follows: The temperature was 720 °C, the time was 12 h, and the heating rate was 2 °C / min; The molar ratio of the lithium hydroxide monohydrate to the precursor material of the surface-coated zirconium hydroxide is 1.0-1.03, wherein the molar amount of the precursor material of the surface-coated zirconium hydroxide is calculated as the sum of the molar amounts of each metal element therein.
2. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the soluble zirconium salt in the solution A is 1×10 -4 ~1 mol / L; The solution A is obtained by dissolving the soluble zirconium salt at 5-120°C.
3. The preparation method according to claim 1 or 2, characterized in that: In step S2, the concentration of the precipitant 1 is 3×10 -4 ~3 mol / L; The concentration of the precipitant 2 is 1.5×10 -4 ~1.5 mol / L; The solution A and the solution B are prepared by using anhydrous ethanol with a volumetric water content of ≤0.4%.
4. The preparation method according to claim 1 or 2, characterized in that: In step S4, the reaction temperature is 5-120°C and the reaction time is 0.5-48 h.
5. The preparation method according to claim 1 or 2, characterized in that: In step S6, the mixing method is wet mixing or dry mixing; The solvent used in the wet mixing is at least one of ethanol, isopropanol or methanol.
6. The preparation method according to claim 1 or 2, characterized in that: In step S6, the calcination atmosphere is at least one of air and oxygen.
7. A positive electrode material prepared by the method according to any one of claims 1 to 6.
8. Use of the positive electrode material according to claim 7 in preparing positive electrode materials for lithium-ion batteries.
9. A lithium ion battery, wherein the positive electrode material is the positive electrode material according to claim 7.
Citation Information
Patent Citations
Nickel-cobalt-manganese ternary precursor, positive electrode material and preparation method
CN114229922A
Preparation method of positive electrode material and positive electrode material
CN115312721A